A taphonomic analysis of PTK (Bed I, Olduvai Gorge) and its bearing on the interpretation of the dietary and eco-spatial behaviors of early humans. (15th January 2023) - Organista, Elia; Moclán, Abel; Aramendi, Julia; Cobo-Sánchez, Lucía; Egeland, Charles P.; Uribelarrea, David; Martín-Perea, David; Vegara-Riquelme, Marina; Hernández-Vivanco, Lucía; Gidna, Agness; Mabula, Audax; Baquedano, Enrique; et al.
Abstract: Here, we present a thorough taphonomic analysis of the 1.84 million-year-old site of Phillip Tobias Korongo (PTK), Bed I, Olduvai Gorge. PTK is one of the new archaeological sites documented on the FLK Zinj paleolandscape, in which FLK 22 level was deposited and covered by Tuff IC. Therefore, PTK is pene-contemporary with these sites: FLK Zinj, DS, AMK and AGS. The occurrence of these sites within a thin clay unit of ∼20 cm, occupying not only the same vertically discrete stratigraphic unit, but also the same paleosurface, with an exceptional preservation of the archaeological record in its primary depositional locus, constitutes a unique opportunity to explore early hominin behavioral diversity at the most limited geochronological scale possible. The Olduvai Bed I sites have been the core of behavioral modelling for the past half a century, and the newly discovered sites, excavated with 21st century technology, will increase significantly our understanding of early human adaptive patterns. Here, we present PTK as another assemblage where faunal resources were acquired by hominins prior to any carnivore, and where stone-tool assisted bulk defleshing was carried out. The abundance of juvenile individuals extends our understanding, as in Kanjera (Kenya), about the hunting skills of early Homo sensu lato . The increasing number of sites, where bulk defleshing of small and medium-sized carcasses took place is underscoring the importance of meat in the diets of some of the early hominins, and their patterned use of the space for food processing and consumption. The patterning emerging has a profound importance for the evolution of some of the features that have traditionally been used to identify the behavior of the genus Homo . Highlights: The new site of PTK, Bed I, Olduvai Gorge, Tanzania (c. 1.84 Ma) shows well-preserved evidence of hominin meat eating. Machine learning methods are applied to discern the agent of bone breakage. Butchery marks and machine learning provide information about past carnivore and hominin behavior. The abundance of young individuals suggests that the hominins employed a selective hunting strategy.